Resection Interposition Arthroplasty for Failed Distal Ulna Resections - Papatheodorou, Loukia K.; Rubright, James H.; Kokkalis, Zinon T.; Sotereanos, Dean G. (Journal of Wrist Surgery, 2013)
The major complications of distal ulna resection, the Darrach procedure, are radioulnar impingement and instability. High failure rates have been reported despite published modifications of the Darrach procedure. Several surgical techniques have been developed to treat this difficult problem and to mitigate the symptoms associated with painful convergence and impingement. No technique has demonstrated clinical superiority. Recently, implant arthroplasty of the distal ulna has been endorsed as an option for the management of the symptomatic patient with a failed distal ulna resection. However, there are concerns for implant longevity, especially in young, active adults. Resection interposition arthroplasty relies on interposition of an Achilles tendon allograft between the distal radius and the resected distal ulna. Although this technique does not restore normal mechanics of the distal radioulnar joint, it can prevent painful convergence of the radius on the ulna. Achilles allograft interposition arthroplasty is a safe and highly effective alternative for failed distal ulna resections, especially for young, active patients, in whom an implant or alternative procedure may not be appropriate.
Keywords: Achilles allograft; distal ulna; failed Darrach; radioulnar impingement